Digitization and Development: Property Rights Security, and Land and Labor Markets. Issue 1 (21st July 2021) - Beg, Sabrin
Abstract: I test the land and labor market effects of a property rights reform that computerized rural land records in Pakistan, making digitized records and automated transactions accessible to agricultural landowners and cultivators. Using the staggered roll-out of the program, I find that while the reform does not shift land ownership, landowning households are more likely to rent out land and shift into non-agricultural occupations. At the same time, cultivating households have access to more land, as rented in land and overall farm size increase. I construct measures of farmer-level total factor productivity (TFP) and marginal product of land, and demonstrate evidence of improved allocative efficiency as land is redistributed toward more productive farmers. Aggregate district-level production data suggest a reduction in the dispersion of marginal products of land and an improvement in productivity. The results have implications for both the allocation of land across farmers and the selection of labor into farming, demonstrating that agricultural land market frictions present a constraint to scale farming and structural change in developing countries.